Patients With Long-QT Syndrome Caused by Impaired hERG-Encoded Kv11.1 Potassium Channel Have Exaggerated Endocrine Pancreatic and Incretin Function Associated With Reactive Hypoglycemia. Issue 18 (2nd May 2017) - Hyltén-Cavallius, Louise; Iepsen, Eva W.; Wewer Albrechtsen, Nicolai J.; Svendstrup, Mathilde; Lubberding, Anniek F.; Hartmann, Bolette; Jespersen, Thomas; Linneberg, Allan; Christiansen, Michael; Vestergaard, Henrik; Pedersen, Oluf; Holst, Jens J.; et al.
Abstract : Background: Loss-of-function mutations in hERG (encoding the Kv 11.1 voltage-gated potassium channel) cause long-QT syndrome type 2 (LQT2) because of prolonged cardiac repolarization. However, Kv 11.1 is also present in pancreatic α and β cells and intestinal L and K cells, secreting glucagon, insulin, and the incretins glucagon-like peptide-1 (GLP-1) and GIP (glucose-dependent insulinotropic polypeptide), respectively. These hormones are crucial for glucose regulation, and long-QT syndrome may cause disturbed glucose regulation. We measured secretion of these hormones and cardiac repolarization in response to glucose ingestion in LQT2 patients with functional mutations in hERG and matched healthy participants, testing the hypothesis that LQT2 patients have increased incretin and β-cell function and decreased α-cell function, and thus lower glucose levels. Methods: Eleven patients with LQT2 and 22 sex-, age-, and body mass index–matched control participants underwent a 6-hour 75-g oral glucose tolerance test with ECG recording and blood sampling for measurements of glucose, insulin, C-peptide, glucagon, GLP-1, and GIP. Results: In comparison with matched control participants, LQT2 patients had 56% to 78% increased serum insulin, serum C-peptide, plasma GLP-1, and plasma GIP responses ( P =0.03–0.001) and decreased plasma glucose levels after glucose ingestion ( P =0.02) with more symptoms of hypoglycemia ( P =0.04). Sixty-three percent of LQT2 patients developed hypoglycemic plasma glucose levels (<70 mg/dL) versus 36% control participants ( P =0.16), and 18% patients developed serious hypoglycemia (<50 mg/dL) versus none of the controls. LQT2 patients had defective glucagon responses to low glucose, P =0.008. β-Cell function (Insulin Secretion Sensitivity Index-2) was 2-fold higher in LQT2 patients than in controls (4398 [95% confidence interval, 2259–8562] versus 2156 [1961–3201], P =0.03). Pharmacological Kv 11.1 blockade (dofetilide) in rats had similar effect, and small interfering RNA inhibition of hERG in β and L cells increased insulin and GLP-1 secretion up to 50%. Glucose ingestion caused cardiac repolarization disturbances with increased QTc intervals in both patients and controls, but with a 122% greater increase in QTcF interval in LQT2 patients ( P =0.004). Conclusions: Besides a prolonged cardiac repolarization phase, LQT2 patients display increased GLP-1, GIP, and insulin secretion and defective glucagon secretion, causing decreased plasma glucose and thus increased risk of hypoglycemia. Furthermore, glucose ingestion increased QT interval and aggravated the cardiac repolarization disturbances in LQT2 patients. Clinical Trial Registration: URL:http://clinicaltrials.gov . Unique identifier: NCT02775513. Abstract : Supplemental Digital Content is available in the text.